The Last Mile: Safety Management Implementation in Construction Sites - Tingshen Zhao; Seyed Ebrahim Kazemi; Wen Liu; Miao Zhang (Advances in Civil Engineering)
To deepen the understanding of the construction safety accidents rules as well as identify and cure the crux of construction safety management failures in China, we analyzed the status quo of safety management and identified the “last mile” problem, that is, the failure of implementation of the extensive legal and regulatory systems on the construction site. The safety factors were then extracted based on a questionnaire consisting of 34 items. Through factor analysis and ranking correlation, five human factors were found to be the greatest challenge and leverage point of safety management at construction sites. Accordingly, a novel safety management framework was proposed and tested as part of the Wuhan-Shenzhen highway project. Expert auditing confirmed that the proposed framework could substantially improve the construction safety performance and thus bridge the “last mile” of safety management implementation.